Identification of Prolyl isomerase Pin1 as a novel positive regulator of YAP/TAZ in breast cancer cells - Khanal, Prem (Sci Rep, 2019)
The Hippo signalling pathway plays very important roles in tumorigenesis, metastasis, organ size control, and drug resistance. Although, it has been shown that the two major components of Hippo pathway, YAP and TAZ, play very crucial role in tumorigenesis and drug resistance, the exact molecular mechanisms are still unknown. Recently, we have shown that the prolyl isomerase Pin1 regulates the activity of Hippo pathway through interaction with Hippo component LATS kinase. Thus we asked if Pin1 is also able to interact with other Hippo pathway components. Therefore, in order to investigate whether Pin1 can interacts with other components of the Hippo pathway, we performed GST-pull down and co-immunoprecipitation (Co-IP) assays and have identified two Hippo components YAP and TAZ oncoproteins as novel binding partner of Pin1. We found that Pin1 interacts with YAP/TAZ in a phosphorylation-independent manner and WW domain of Pin1 is necessary for this interaction. Moreover, by using real time qRT-PCR, Cycloheximide chase, luciferase reporter, cell viability and soft agar assays, we have shown that Pin1 increases the tumorigenic and drug-resistant activity of YAP/TAZ through stabilization of YAP/TAZ at protein levels. Together, we have identified Pin1 as a novel positive regulator of YAP/TAZ in tumorigenesis and drug resistance of breast cancer cells. These findings will provide a significant contribution for targeting the Pin1-YAP/TAZ signaling for the successful treatment of tumorigenesis and drug resistance of breast and other cancers in the future.